Pengaruh Model Discovery Learning Berbantuan Educaplay Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPAS - Alifah Nur Hasanah; Hisny Fajrussalam; Nenden Permas Hikmatunisa (LPPM Institut Pendidikan Nusantara Global, 2026)
This study was based on the low critical thinking skills of fourth-grade students in IPAS (Ilmu Pengetahuan Alam dan Sosial) learning at an elementary school in Purwakarta. This study aimed to analyze the effect and improvement of Discovery Learning assisted by Educaplay on students' critical thinking skills. The research used a quasi-experimental method with a nonequivalent control group design involving 48 students. Data were collected through essay-based pretest and posttest and analyzed using normality, homogeneity, regression, t-test, and N-Gain tests. The results showed that Discovery Learning assisted by Educaplay had a positive effect of 59.8%, higher than Guided Inquiry in the control class (35.9%). The N-Gain score of the experimental class (0.6766) was also higher than the control class (0.5426). Thus, Discovery Learning assisted by Educaplay is effective for improving students' critical thinking skills in IPAS learning.